The Impact of Problem-Based Learning on Teaching The Aspect Of Organization In ESP Writing - Ivana Martinović Barbul (English Language Teaching Methodology, 2026)
The rapidly evolving demands of the global workplace require higher education to move beyond traditional rote learning toward methods that mirror real-world professional challenges. By placing students at the center of authentic scenarios, problem-based instruction serves as a bridge between classroom theory and the complex communication tasks required in specialized careers. Problem-based instruction was developed to foster students’ intrinsic motivation, problem-solving and collaboration skills, creativity, as well as their capacity for independent research, analysis, and reasoning. The research presented in this dissertation sought to investigate the extent to which problem-based instruction enhances the acquisition of the global aspect of writing organization in English for Specific Purposes (ESP) courses. This focus is particularly relevant, as prior studies rarely examine specific writing components, instead tending to address writing development in a more general sense. In accordance with the defined research problem, aim, and tasks, a causal method was applied in the study— a controlled experimental design with two groups. The group exposed to the experimental condition covered the basic features of business style through a previously designed teaching unit prepared according to the principles of structuring a problem-based lesson. The same content was taught in the control group, but through a lecture-demonstration instructional method. The results of the paired-samples t-test revealed that problem-based learning is highly beneficial model when the goal is to develop writing style in students learning English for Specific Purposes.